Identification of the key variables that can be estimated using remote sensing data and needed for Water Footprint (WF) assessment - Romaguera, Mireia; Toulios, Leonidas; Stancalie, Gheorghe; Nertan, Argentina; Spiliotopoulos, Marios; Struzik, Piotr; Calleja, Eman J.; Papadavid, George (My University, 2014)
Accurate assessment of water use is an important issue in a globally changing climate and environment, where water is becoming a scarce but essential resource. The concept "?Water Footprint (WF) of a crop is defined as the volume of water consumed for its production, where green and blue WF stand for rain and irrigation water usage, respectively. This indicator provides valuable information for a global assessment of how water resources are used. Remote sensing (RS) provides physically-based, worldwide, and consistent spatial information over space and time, and has been used in hydrological applications in order to estimate relevant variables at different temporal and spatial scales. The paper focuses on exploring and exploiting the potential of using RS techniques and data for WF assessment in agriculture. Based on recent papers initiated in this research topic the investigation focuses on how variables needed in the calculation of water footprint are obtained (based on non RS and on RS approaches), on identifying the inputs required for estimating the WF of crops and whether it is feasible to integrate various RS approaches. The results of this study demonstrate the usefulness of satellite data for water footprint assessment, which were obtained by the Remote Sensing Working Group in the framework of the ESSEM COST Action ES1106, "Assessment of EUROpean AGRIculture WATer use and trade under climate change"? (EURO-AGRIWAT). © 2014 SPIE.
Keywords: agriculture; biophysical variables; remote sensing; water footprint